Analysis of Local Coffee Shop Marketing Agility and Customer Retention Amidst of Starbucks Boycott in Padang - Danis Ganeru; Vera Pujani; Yulia Hendri Yeni (Dinasti Review, 2025)
This study aims to examine the segmentation, marketing agility, and customer retention of local coffee shop in Padang. The phenomena that discussed in this research are boycott movement of several brand particularly Starbucks and Fear of Failure. This research adopts a qualitative approach which aims to understand symptoms that do not require quantitative measurement. The data used in this research is derived from interview with the owner of local coffee shop in Padang with the total of 5 informant. The data analysis process is compiling data obtained from interviews and process it with Nvivo12. Boycott was found to have no influences towards Marketing Agility and Customer Retention of Local Coffee Shop in Padang. Nonetheless Fear of Failure was found to have influences towards Marketing Agility and Customer Retention of Local Coffee Shop in Padang.